Reducing meadow damage in determining the Leaf Plastochrone Intervals (LPI) of Enhalus acoroides (L. f.) Royle and increasing statistical power in assessing site-scale LPI variability - de Venecia, Mary Bernadette B.; Rollon, Rene (2011)
The leaf plastochrone interval (LPI)—the duration between the initiation of two successive leaves—is central to various age-based studies for understanding seagrass productivity, growth and meadow maintenance. The conventional leaf-marking method of determining LPI, however, requires an observation period equivalent to the LPI of the species. Such observation period, when applied to the large tropical seagrass Enhalus acoroides, is long (26–35 d) and increases the risk of losing marked shoot samples. In this study that covered a 14-d observation period, we compared LPI estimates obtained through the conventional- and individual-based leaf growth methods. The conventional method required a collective sample of at least 80 shoots to calculate for a single LPI value with sufficient accuracy. The individual-based leaf growth procedure, which relies on the length difference and growth rates of the two youngest leaves in a shoot, yielded comparable LPI estimates, with superior replication. The study showed that the latter method was independent of the LPI as a requisite observation period, allowed discrete determinations of LPI from an individual shoot and consequently increased replication by 80%, enabling robust statistical testing. A sample size of 30 shoots per transect was found to be sufficient to allow the detection of within-meadow spatial variability. Subject to a few refinements, the applicability of the individual-based method to determine the LPI of Enhalus acoroides has enormous implications in reducing meadow damage, while increasing the statistical power with high spatio-temporal resolution when assessing LPI variability.
Keywords: Plant morphology